The Impact of Financial Report Accessibility on The Accountability Of Regional Financial Management: A Systematic Literature Review - Heni Suryanti; Khairul Saleh L. Tobing; Syamsudin; Kumba Digdowiseiso; Nur Haiza Muhammad Zawawi (CV ODIS, 2023)
This research investigates the results of a literature study regarding the impact of financial report accessibility on regional financial management accountability. The research method used was a Systematic Literature Review (SLR), which involved identifying 10 accredited national journals. This study revealed significant findings in the Indonesian context. The results show that the presentation of financial reports that are accurate and by accounting standards (SAP) as well as a high level of accessibility to regional financial reports have a positive impact on the accountability of regional financial management. In addition, a good internal control system also supports increased accountability, while the influence of financial report accessibility on accountability tends to be complex and context-specific. However, individual factors such as the competence of village government officials play an important role in increasing the level of accountability. The low competence of village officials is considered to be one of the main causes of the low level of accountability in managing village funds. Within the accountability framework, this research highlights the importance of implementing an internal control system in organizations to ensure effectiveness, compliance with regulations, and transparency in public financial management. Information accessibility may not be sufficient as a driver of accountability, perhaps because the way information is delivered is currently limited to simple media. Nevertheless, this study provides insight for the government and researchers to consider these aspects in improving and planning policies to increase transparency and accountability in regional financial management